Potential Employees’ Impression Management Tactics and Human Resource Management Professionals’ Perspectives - Yağmur Bakanoğlu; Emel Esen; Selin Karaca Varinlioğlu (Istanbul Management Journal)
This research aims to determine the impression management tactics used by potential employees that are important to employers in the job market, particularly in their curriculum vitaes (CVs) and interviews during the application process, and to identify which tactics are the most important to human resources (HR) specialists. The study has employed within its scope semi-structured interviews that allow a thorough examination of the participants’ feelings, attitudes, and thoughts with 45 potential employees and eight HR professionals. The study findings reveal that potential employees mostly prefer the tactics of building a favorable image, self-promotion, and supplication, whereas they use exemplification tactics less. Similar to these results, HR professionals also highlighted the tactics of building a favorable image, self-promotion, and supplication in recruitment interviews. The study results are expected to be beneficial for creating a more positive image of potential candidates in the labor market, both during the recruitment interviews and the job application stage.